Novel carbon dioxide removals techniques must be integrated into the European Union's climate policies - Mathias Fridahl; Felix Schenuit; Liv Lundberg; Kenneth Möllersten; Miranda Böttcher; Wilfried Rickels; Anders Hansson (Communications Earth & Environment, 2023)
Given the escalating climate crisis, the task of integrating novel carbon dioxide removals into the European Union's climate policy is urgent and long overdue. Here, we argue that there is a window of opportunity for responding now, and put forward a solution.
Keywords: 330